Pendidikan Jasmani Sekolah DasarSebagai Wahana Kompensasi Gerak Anak - M. Hamid Anwar (Jurnal Pendidikan Jasmani Indonesia, 2005)
In the vast development of civilization there is a big space for technology totake part. In the process, not all of the development has come to a positive influence.One of the example is a children world, playing which pressured by the technology.Traditional games have been replaced by new games with technology that makechildren are less physically active. In the end, many physical problems for childrenoccurred. This problem has been an obstacle to have optimum growth for the childcause by minimum movement such as overweight and obesity.Physical education is an alternative solution to the problems occurred. Physicaleducation has become a compensation to stimulate, motivate and accommodatechildren motor needs.Kata Kunci: Pendidikan Jasmani, Kompensasi, Gerak.